Desdobramentos de curto e médio prazo da crise atual - Luciana Acioly; Milko Matijascic; Emilio Chernavsky; Maria Pi\~nón; Rodrigo Pimental Ferreira Le\~ao (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– The current financial crisis has deepened during the end of 2008. The multinational corporations (MNCs) are trying to adapt themselves, the international organizations are debating possible solutions, and the governments are increasing their capacity to intervene in the economy. This work presents the origins of the crisis and some of its characteristics. It also shows the recent trends on selected countries` macroeconomic indicators, as well as the crisis effects on short term economic projections. Then it indicates the policies adopted by some countries, the reactions of MNCs, and actions and positions of multilateral organizations to promote a new financial regulatory framework.The work considers that the source of the problem is in the financial sector. However, due to the effects on the economy`s real sector, the growth recovery will demand a strong action toward more political cooperation between the agents involved.
Keywords: F01; F42; F33; 330